1979
DOI: 10.1073/pnas.76.11.5430
|View full text |Cite
|
Sign up to set email alerts
|

RNA ligase reaction products in plasmolyzed Escherichia coli cells infected by T4 bacteriophage.

Abstract: Searching for a physiological role of T4 RNA ligase [polyribonucleotide synthetase (ATP); poly(ribonucleotide):poly(ribonucleotide) ligase (AMP-forming), EC 6.5.1.3] activity, we developed an acellular system of plasmolyzed Escherichia coli cells infected by T4 bacteriophage. Upon incubation of this system with 2p was transferred into a large number of polyribonucleotides, mostly up to 300-400 residues long. The bulk of 32P in the product polyribonucleotides was found in 5'-terminal phosphate groups, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1980
1980
1987
1987

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…1 and 3). Such a correlation lends further support to our previous hypothesis about a T4-induced pathway of host tRNA breakage and reunion (5,10). According to this hypothesis (Fig.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…1 and 3). Such a correlation lends further support to our previous hypothesis about a T4-induced pathway of host tRNA breakage and reunion (5,10). According to this hypothesis (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…1] has been well characterized in vitro (2,3), but its role in phage infection still needs to be determined (4)(5)(6). We have previously suggested that RNA ligase and additional T4 enzymes, such as polynucleotide kinase (EC 2.7.1.78; ref.…”
mentioning
confidence: 99%
“…An intriguing property of the false revertants is that they are very sensitive to hydroxyurea, an inhibitor of nucleotide metabolism, leaving the possibility that the gene 63 product may have some role in nucleotide metabolism. Recently, David et al (4) have suggested that the RNA ligase activity of the gene 63 product may be involved in the processing of host tRNA's into novel tRNA species during infection.…”
Section: Discussionmentioning
confidence: 99%
“…The ATP binding site is very specific; only dATP can be substituted in the ligase reaction, and does so very poorly [5]. The acceptor and donor binding sites are less specific with regard to oligonucleotide composition ; however, the minimum acceptor must be a trinucleoside bisphosphate, and the minimum donor a mononucleoside 3',5'-bisphosphate [6-91.…”
mentioning
confidence: 99%